Women, educational policy-making, and administration in England : authoritative women since 1800 - Goodman, Joyce, 1946-; Harrop, Sylvia A. (Routledge research in gender and history, 2000)
Opening up the role of women in policy-making as a new field of study, this book takes the example of women in education as its focus. It examines the work, attitudes and actions of women in education over two centuries.